Design of Reinforced Concrete Structure of 6-story Ayani Square Office Shop Building with Intermediate Moment Resisting Frame System - Hakika, Ifkhyna Khaula; Elvira, Elvira; Yusuf, Muhammad; Faisal, Faisal (Fakultas Teknik Universitas Tanjungpura, 2024)
Buildings should be designed for strength and longevity, considering various loads like live, dead, and wind. In Kalimantan Barat, particularly Pontianak City, mild to moderate earthquakes are common, making it crucial to follow SNI 1726-2019 regulations for earthquake-resistant design. This includes using a Moment Resisting Frame system that allows the structure to absorb lateral forces and prevent sudden collapse. The chosen system reflects the building's function and soil data, ensuring it meets safety and practicality standards. For the Ayani Square Building, intermediate Moment Resisting Frames with seismic design category C were employed. The structure must adhere to SNI 1726-2019 for safety, with reinforcement designed per SNI 2847-2019 to enhance robustness. Spun piles are used in the foundation to provide stability and load-bearing capacity, effectively reducing seismic impact in moderate hazard zones.Keywords: Structural Analysis, Reinforced Concrete Structures, Intermediate Moment Resisting Frame Systems, and Seismic Design Category C